Thermodynamic, sustainability, environmental and damage cost analyses of jet fuel starter gas turbine engine. (15th March 2023) - Abdalla, Muftah S.M.; Balli, Ozgur; Adali, Osama H.; Korba, Peter; Kale, Utku
Abstract: Jet Fuel Starter Gas Turbine Engine (JFS-GTE) used on a military aircraft is explored for on design mode and off design mode configurations at rated capacity cycles employing thermodynamic, environmental, sustainability, emission impact, and environment pollution cost analyzing. The engine generates 157.94 kW-shaft power at on design case whilst it produces 187.05 kW-shaft power at off design case. In this situation, the energy efficiency of JFS-GTE is accounted for 15.81% in an on design case and 17.01% in an off design case while the exergetic efficiency of JFS-GTE is estimated to be 14.89% in on design case and 16.02% at off design case. Using the environmental analyzing method, the enviro-effect factor and ecology-effect factor of JFS-GTE are found as 5.716 and 6.716 at on design case and 5.241 and 6.241 at off design case. Then, exergetic sustainability index and sustainable efficiency factor of JFS-GTE are computed as 0.175 and 1.175 at on design mode and 0.191 and 1.191 at off design mode. Afterward, the specific emission impact (sei) is computed as 6.555 mPts/GJ at on design and 5.621 mPts/GJ at off design mode. Finally, the specific environmental damage cost is determined to be 0.045 $/GJ at on design and 0.041 $/GJ at off design. These results show that JFS-GTE operates more energy and exergy efficiency, is more sustainable engine, has a low environmental impact and less environmental damage cost formation at off design case. Highlights: Jet fuel Starter Gas Turbine Engine (JFS-GTE) is investigated for on design and off design modes. The environmental and sustainability analyses of JFS-GTE are studied in a detail. Emission impact analysis is done to obtain the emissions' harmful levels on environment. Environmental damage cost analysis is realized to track cost formation of pollutants.